Multifunctional bimetallic MOF with oxygen vacancy synthesized by microplasma for rapid total antioxidant capacity assessment in agricultural products - Yi Xia; Juan He; Long Tang; Miao Hu; Jie Zhou; Yao-Yu Xiao; Zhi-Chao Jiang; Xue Jiang (Food Chemistry: X, 2024)
The assessment of total antioxidant capacity (TAC) is crucial for evaluating overall antioxidant potential, predicting the risk of chronic diseases, guiding dietary and nutritional interventions, and studying the effectiveness of antioxidants. However, achieving rapid TAC assessment with high sensitivity and stability remains a challenge. In this study, Ce/Fe-MOF with abundant oxygen vacancies was synthesized using microplasma for TAC determination. The microplasma synthesis method was rapid (30 min) and cost-effective. The presence of oxygen vacancies and the collaboration between iron and cerium in Ce/Fe-MOF not only enhanced the catalyst's efficiency but also conferred multiple enzyme-like properties: peroxidase-like, oxidase-like, and superoxide dismutase mimetic activities. Consequently, a simple colorimetric assay was established for TAC determination in vegetables and fruits, featuring a short analysis time of 15 min, a good linear range of 5–60 μM, a low detection limit of 1.3 μM and a good recovery of 91 %-107 %. This method holds promise for rapid TAC assessment in agricultural products.